Impact of traffic-related air pollution on acute changes in cardiac autonomic modulation during rest and physical activity: a cross-over study - Cole-Hunter,T; Weichenthal,S; Kubesch,N; Foraster,M; Carrasco-Turigas,G; Bouso,L; Martinez,D; Westerdahl,D; de,Nazelle A; Nieuwenhuijsen,M (Journal of Exposure Science and Environmental Epidemiology, 2015)
People are often exposed to traffic-related air pollution (TRAP) during physical activity (PA), but it is not clear if PA modifies the impact of TRAP on cardiac autonomic modulation. We conducted a panel study among 28 healthy adults in Barcelona, Spain to examine how PA may modify the impact of TRAP on cardiac autonomic regulation. Participants completed four 2-h exposure scenarios that included either rest or intermittent exercise in high- and low-traffic environments. Time- and frequency-domain measures of heart rate variability (HRV) were monitored during each exposure period along with continuous measures of TRAP. Linear mixed-effects models were used to estimate the impact of TRAP on HRV as well as potential effect modification by PA. Exposure to TRAP was associated with consistent decreases in HRV; however, exposure–response relationships were not always linear over the broad range of exposures. For example, each 10 μg/m3 increase in black carbon was associated with a 23% (95% CI: −31, −13) decrease in high frequency power at the low-traffic site, whereas no association was observed at the high-traffic site. PA modified the impact of TRAP on HRV at the high-traffic site and tended to weaken inverse associations with measures reflecting parasympathetic modulation (P≤0.001). Evidence of effect modification at the low-traffic site was less consistent. The strength and direction of the relationship between TRAP and HRV may vary across exposure gradients. PA may modify the impact of TRAP on HRV, particularly at higher concentrations.